The Role of Stakeholder Involvement in Enhancing Safe Drinking Water Infrastructure: An Interpretative Structural Modeling Approach - Rahmanea, Awlya; Rarasati, Ayomi Dita (CSID Journal of Infrastructure Development, 2024)
One of the primary goals listed in the Sustainable Development Goals (SDGs) is to “Achieve universal and equitable access to safe and affordable drinking water for all,” as stated in SDG 6.1. To obtain this goal, the Government of Indonesia has developed the 2020-2024 National Medium-Term Development Plan (RPJMN), which has set specific targets including achieving 100% access to decent drinking water, 15% access to safe drinking water, and establishing 10 million house connections. The Ministry of National Development Planning has established a goal of achieving 45% access to safe drinking water by 2030 as part of the SDGs. However, as per the World Health Organization (WHO), Indonesia is projected to attain a 30% level of access to safe drinking water by 2022, which falls short of the objective set for 2030. Therefore, this study aims to identify the stakeholders involved in achieving safe drinking water goals and the factors that affect the achievement of access to safe drinking water. The methods employed include interviews to identify and map stakeholders, Geometric Mean (GM) analysis to assess the level of influence and interest of stakeholders, and Interpretative Structural Modelling (ISM) to determine the influence level of each factor. The findings reveal that seven agencies are involved as stakeholders. The primary stakeholders in the "Manage Closely" quadrant include the Ministry of National Development Planning, the Ministry of Public Works and Housing, and the Local Government. Additionally, 23 factors were found to have an impact on the provision of safe drinking water. The ISM analysis indicated that the most influential factors were “Restrictions on authority related to regional autonomy and power sharing between institutions/ministries,” “The number of stakeholders involved,” and “Regulations and policies related to the procurement of safe drinking water supply.”